Trends in blood transfusion and causes of blood wastage: a retrospective analysis in a teaching hospital - Ju-huei Chien; Chao-yuan Yao; Hui-fen Chen; Tsing-Fen Ho (BMC Health Services Research)
Abstract Background Blood is a vital medical resource that is sourced from primarily nonremunerated donations. As Taiwan faces an aging population, increasing medical demands pose new challenges to blood resource management. Trend analysis can improve blood supply chain management and allocate blood resources more efficiently and cost-effectively. Methods A retrospective review was conducted from 2011–2023 in a teaching hospital to examine the utilization and wastage of blood products. Data were collected from hospital information system and blood wastage reports, categorized by cause, and analyzed via SAS software version 9.3. Results The hospital released 424,197 units of blood products, with leukocyte-reduced red blood cells accounting for 140,971 units. The highest annual wastage rate was 0.29% in 2011, and the annual average was 0.08%. Fresh frozen plasma (36.3%), platelet concentrates (15.2%), and cryoprecipitate (14.3%) were the most frequently discarded. Major causes of wastage included excessive or inappropriate orders (22.3%), inability to reissue blood before expiration (16.7%), and incorrect orders (14.6%). Platelet wastage was caused primarily by improper storage, while thawed plasma could not be repurposed. Utilization of leukocyte-reduced blood products has increased, leading to a significant reduction in transfusion reactions from 1.8% in 2011 to 0.6% in 2023. Conclusions The study highlights that blood wastage often stems from human error or improper storage conditions. The leading cause of platelet product disposal is incorrect storage temperatures, along with the inability to repurpose thawed plasma for plasma products. Importantly, the increased adoption of prestorage leukocyte-reduced blood products has significantly mitigated transfusion-related reactions. We emphasize that continuous education for healthcare professionals and enhanced inventory monitoring are critical to minimize wastage and enhance transfusion quality.